ONCE AGAIN THE TERM MA???’ IN ZECHARIAH 9:1; 12:1 AND IN MALACHI 1:1: WHAT IS ITS SIGNIFICANCE? - K W Weyde (Acta Theologica)
The article argues that ma???’ in Zechariah 9:1; 12:1 and in Malachi 1:1 refers to written prophecy. The phrase d?bar yhwh, which follows this term, gives authority to this phenomenon, as do the frequent occurrences of formulas marking divine speech in the Book of Malachi, and to some degree in Zechariah 9-14. In addition, the lack of divine revelation in these materials indicates that prophecy in the old sense of the word changed some time after the prophets Haggai and Zechariah conveyed their message. However, some features of Malachi 1:1, Zechariah 11:4, and Malachi 1:2-5 provide continuity with these prophets and with pre-exilic prophecy (Hos. 12:11, 14; Zech. 7:7; Hag. 1:1, 3; 2:1), as well as with Moses and the law. Ma???’ in Zechariah 9:1; 12:1 and in Malachi 1:1 covers these aspects of prophecy and connects to the oracles concerning the nations in Isaiah 13-23, which are introduced by the same term.